Center Line Slope Analysis in Two-Dimensional Electronic Spectroscopy - Šanda, František; Perlík, Václav; Lincoln, Craig N; Hauer, Jürgen (The journal of physical chemistry. A, 2015)
Center line slope (CLS) analysis in 2D infrared spectroscopy has been extensively used to extract frequency-frequency correlation functions of vibrational transitions. We apply this concept to 2D electronic spectroscopy, where CLS is a measure of electronic gap fluctuations. The two domains, infrared and electronic, possess differences: In the infrared, the frequency fluctuations are classical, often slow and Gaussian. In contrast, electronic spectra are subject to fast spectral diffusion and affected by underdamped vibrational wavepackets in addition to Stokes shift. All these effects result in non-Gaussian peak profiles. Here, we extend CLS-analysis beyond Gaussian line shapes and test the developed methodology on a solvated molecule, zinc phthalocyanine. We find that CLS facilitates the interpretation of 2D electronic spectra by reducing their complexity to one dimension. In this way, CLS provides a highly sensitive measure of model parameters describing electronic-vibrational and electronic-solvent interaction.